Analisis Pengetahuan dengan Perilaku Merokok pada Remaja - Budi Kurniawan; Mayang Sari Ayu (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2023)
Smoking behavior is a problem that is detrimental to public health. Indonesia is a country with the third most active smokers globally. The increase in the number of smokers is increasing in adolescents. The purpose of this study was to determine the relationship between knowledge and smoking behavior in adolescents. This type of research is an explanatory research survey with a cross-sectional study approach. The data analysis used was univariate analysis and bivariate analysis with the Chi-Square test statistic at the 95% confidence level. The population of the study was all students at the Harapan Bangsa Private Vocational High School, Tanjung Morawa, North Sumatra Province, amounting to 674 people. Determination of the research sample using the cluster sampling technique of 87 people, of which 33 people (37.9%) were smokers and 54 people were not smokers. The results of this study indicate that the knowledge of most students about smoking is quite good (60%). Based on the results of the statistical test analysis, it was found that there was a relationship between knowledge and adolescent smoking behavior with a value of p = 0.027, OR= 4,688. Suggestion: it is suggested to the Harapan Bangsa Private Vocational High School in Tanjung Morawa to implement a No-Smoking Area in schools. Forming a task force to oversee the implementation of smoking-free areas in the school environment went w